Effects of Delta-9 Tetrahydrocannabinol (THC) on Oocyte Competence and Early Embryonic Development - Misner, Megan J.; Taborek, Afton; Dufour, Jaustin; Sharifi, Lea; Khokhar, Jibran Y.; Favetta, Laura A. (Frontiers in Toxicology, 2021)
Recent changes in legal status and public perception of cannabis have contributed to an increase use amongst women of reproductive age. Concurrently, there is inadequate evidence-based knowledge to guide clinical practice regarding cannabis and its effects on fertility and early embryonic development. This study aimed to evaluate the effects of the primary psychoactive component of cannabis, delta-9 tetrahydrocannabinol (THC), during oocyte maturation, and its impact on the developing embryo. Bovine oocytes were matured in vitro for 24 hours under clinically relevant doses of THC mimicking plasma levels achieved after therapeutic (0.032M) and recreational (0.32M and 3.2M) cannabis use. THC-treated oocytes were assessed for development and quality parameters at both the oocyte and embryo level. Characteristics of oocytes treated with cannabinoid receptor antagonists were also assessed. Oocytes treated with 0.32M and 3.2M THC, were significantly less likely to reach metaphase II (p<0.01) and consequently had lower cleavage rates at day 2 post-fertilization (p<0.0001). Treatment with cannabinoid receptor antagonists restored this effect (p<0.05). Oocytes that did reach MII showed no differences in spindle morphology. Oocytes treated with 0.032M THC had significantly lower connexin mRNA (p<0.05) (correlated with decreased quality), but this was not confirmed at the protein level. At the blastocyst stage there were no significant differences in developmental rates or the proportion of trophectoderm to inner cell mass cells between the control and treatment groups. These blastocysts, however, displayed an increased level of apoptosis in the 0.32M and 3.2M groups (p<0.0001). Our findings suggest a possible disruptive effect of cannabis on oocyte maturation and early embryonic development.